Horta orgânica na fundação de bem estar com crianças em risco de vulnerabilidade social - Bonin, Camilla Cristine Guerra (2014)
This study characterizes the effects of the implementation of an agro ecological garden in welfare foundation, promoting therapeutic and instructive activities for children at risk of social vulnerability of the city of Pato Branco - PR. The goal is to raise the children environmental awareness, turning them into multipliers of this practice outside the school environment, to have an outdoor activity that allows the interaction with others and provides the formation of active and conscious citizens. Initially, theoretical classes were given to stress the importance of consuming fruits and vegetables during child development, the effects of pesticides and alternative ways of producing vegetables. The area for growing vegetables was revitalized in order to carry out the practical activities; it was built a 5m x 15m plastic greenhouse, where children could build a worm farm to obtain humus and they made the planting of vegetable seedlings. The results were qualitatively characterized from questionnaires administered before and after the theoretical and practical activities. After the first months of implantation, the answers are already noticeable. There was considerable improvement in the disposal of the waste generated in FUNDABEM, the children have shown receptiveness to new vegetables that were not consumed by them before and also a greater concern for the environment.